Casualty reports : poems - Collins, Martha, 1940- (Pit poetry series., 2022)
"Stylistically innovative, deeply moving, carefully researched, Martha Collins's eleventh volume of poetry combines her well-known attention to social issues with the elegiac mode of her previous book. She focuses here on race, gun violence, recent wars, and, in an extended sequence, the history of coal--first as her ancestors mined it, then from its geological origins to our ecologically threatened present. Casualty Reports is both indictment and lament, a work that speaks forcefully to our troubled history and our present times."--